Novelties in Wood Engineering and Forestry - Lunguleasa, Aurel; Dinulica, Florin; Cosereanu, Camelia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue compiles11 research papers published in the field of forestry and wood processing technology. In particular, this Special Issue highlights the research on timber saw, biomass and waste from resinous branches, forest by-products, log exploitation, the primary processing of round wood in timber with a band saw, the quality of exploited wood, and the role of the forest and forest ecosystem on the environment. Regarding wood science processes, this Special Issue presents works on cutting round wood in timber and veneers, technology 4.0, the manufacture of furniture and musical instruments, acoustical properties, wood biomass, including briquettes and pellets, thermochemical treatments of wood and pellets, finishing processes, and the restoration of cultural heritage objects using classical technologies and chemical materials. A lot of material waste was used to obtain better composites or chemical substances to obtain wood-based composites with better properties and low-level formaldehyde emission.